The Incidence of Overdissipation in Rent-Seeking Contests - Michael R. Baye; Dan Kovenock; Casper G. de Vries (Tinbergen Institute, 1997)
This paper reconsiders Tullock's analysis of rent seeking and wasteful overdissipation. The purpose of this paper is to point outthat even though his original analysis of overdissipation is technically flawed, the definition of overdissipation can bemodified to explain instances in which rational rent-seekersspend more to win a prize than the prize is worth. We showed before that equilibrium mixed strategies in the Tullock game do not permit overdissipation in expectation: the expected total amountspent competing for rents cannot exceed the value of the prize. However, since the equilibrium involves mixed-strategies forparticular realizations of the mixed strategies the total amount spent competing for rents can exceed the value of theprize! In fact, we show that the cross-sectional incidence of overdissipation may be quite high. For a symmetric perfectly discriminating contest (R = ∞), the probability of overdissipation in a symmetric equilibrium ranges from exactly one-half in the two player case to approximately .44 as the number of players approaches infinity.
Keywords: 330; Rent-Seeking; Theorie